A real driver of US-China trade conflict: The Sino-US competition for global hegemony and its implications for the future - Min-hyung Kim (International Trade, Politics and Development (ITPD), 2019)
Purpose - According to the conventional wisdom, trade is not a zero-sum game, but a positive-sum game. By allowing countries to focus on producing the goods that they can produce relatively efficiently, free trade is largely beneficial for everyone involved. Then, why are the world's two largest economies (i.e. the USA and China) currently engaged in a trade war, which is likely to hurt their own economies? What is the driving force for the trade war between the two economic giants? The purpose of this paper is to offer an explanation of the underlying cause of the US-China trade war. Design/methodology/approach - In an effort to make sense of the trade war between the USA and China, the paper draws the insights from the two international relations theories - i.e. hegemonic stability theory and power transition theory. Findings - As China continues to threaten US hegemony in the world in general and East Asia in particular, the Sino-US competition for hegemony will intensify over time. As a result, the trade war between the two countries may persist longer than many anticipate. Further, even if the trade war between the two superpowers ends soon, a similar type of conflict is likely to occur later as long as the Sino-US hegemonic rivalry continues. Originality/value - The central thesis of this paper is that "US fear" about its declining hegemony and China's rapid rise as a challenger of US hegemony is driving a US-launched trade war with China. Since the underlying cause of the trade war between the world's two largest economies is political (i.e. the Sino-US hegemonic rivalry) rather than economic (e.g. US attempts to improve the trade balance with China by imposing tariffs on Chinese goods), the paper contends that the full understanding of the trade war requires close attention to the importance of power competition between the two superpowers.
Keywords: 330; China's rise; Hegemonic stability; Power transition; Sino-US hegemonic competition; Trade war